Korean public's preference for supply security of oil and gas and the impact of protest bidders. (February 2016) - Kim, Jihyo; Kim, Jinsoo; Kim, Yoon Kyung
Abstract: The Korean governmental support for supply security of oil and gas via overseas exploration and production (E&P) projects are publicly criticized because of some poor projects lacking of economic feasibility, even though it should be expanded from a long-term perspective. Applying the contingent valuation, this study investigates the Korean public's preferences for governmental support for overseas oil and gas E&P projects. The result shows that the governmental support for overseas E&P projects rather decreases public utility. The primary reason behind this utility decrease is that some respondents protested to bid because of their resistance toward tax increase without guaranteeing the efficient government support. This result implies that simple tax increases for expansion of the governmental support may bring about public's strong opposition. In order to overcome this public opposition, this study suggests that it is necessary to arouse public understanding of the necessity of overseas oil and gas E&P projects. Highlights: We investigate the Korean public's preferences for an oil and gas supply security. The respondents are willing to pay USD 0.017 per liter of gasoline or diesel. Governmental support for overseas E&P projects decreases the public utility. It is need to increase public understanding of overseas oil and gas E&P projects.